Improving Safety At Small Underground Mines - Proceedings: Bureau Of Mines Technology Transfer Seminar - Robert H. Peters (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This U.S. Bureau of Mines report identifies the types of serious accidents that occur most frequently at small underground coal mines and describes the strategies that could help prevent these accidents. A wide variety of methods for improving safety are suggested, including improvements in the design of equipment, work procedures, work schedules, safety programs, and emergency response plans, as well as techniques for diagnosing the potential hazards associated with new technologies and work procedures. Some of the papers in this volume focus on preventing specific types of mining accidents-ones associated with materials handling (primarily back injuries), equipment maintenance, improper machine guarding, and ground failure during retreat mining. Although the recommendations in this volume are heavily influenced by research performed at underground coal mines in the Appalachian coalfields, most of the papers contain advice that is equally pertinent to almost any type of mine.